A Stretchable and Highly Sensitive Graphene‐Based Fiber for Sensing Tensile Strain, Bending, and Torsion. (19th October 2015) - Cheng, Yin; Wang, Ranran; Sun, Jing; Gao, Lian
Abstract : Wearable sensors are increasingly finding their way into applications of kinesthetic sensing, personal health monitoring, and smart prosthetics/robotics. A graphene‐based composite fiber sensor with a "compression spring" structure is fabricated, featuring the ability of detecting multiple kinds of deformation. This fiber sensor is integrated into wearable sensors for monitoring human activities and intricate movements of robotics successfully.